Membrane-free redox flow cell based on thermally regenerative electrochemical cycle for concurrent electricity storage, cooling and waste heat harnessing of perovskite solar cells - Zhang, H (Elsevier BV, 2023)
10.1016/j.jpowsour.2022.232081